Development of Learning Tools Based on Geogebra-Assisted Inquiry Learning Models to Improve Students' Mathematical Reasoning Abilities - Silalahi, Joshua Pandapotan; Siagian, Pargaulan Pargaulan; Mukhtar, Mukhtar Mukhtar (Study Program of Mathematics Education of Unimed Postgraduate Program, 2024)
The Geogebra-assisted inquiry learning paradigm was created to increase students' mathematical thinking. This research will identify the learning device. This is development research. This study will be done in SMA Negeri 1 Gebang, Jl. Diponogoro, Pekan Gebang, Kecamatan Gebang, Kab. Langkat, North Sumatra 20856. The research found: 1) The device is valid. 2) The device developed is practical with an average value of 3.07 (category